2020
DOI: 10.3390/antibiotics9110765
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Activity of Selected Essential Oils against Staphylococcus spp. Isolated from Human Semen

Abstract: Staphylococcus spp. is not only a commensal bacteria but also a major human pathogen that causes a wide range of clinical infections. Recent evidence suggests that Staphylococcus has the ability to colonize the reproductive system and to affect its structure and functions. The objective of this study was to determine the chemical properties and antibacterial effects of select essential oils (EOs): Amyris balsamifera L., Boswellia carterii Birdw., Canarium luzonicum (Blume) A. Gray, Cinnamomum camphora (L.) J. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 76 publications
3
35
1
Order By: Relevance
“…The oil examined in our study had an α-santalol content slightly lower than literature values of Santalum album oils ( Table 3 ) but higher than the oil obtained from Santalum spicatum . The β-santalol content approximated that determined by Kačániová et al [ 3 ], Panto et al [ 26 ] and Góra and Gibka [ 27 ]. Our results confirm that the examined oil was obtained from Santalum album ; however, it does not fulfill ISO 3518:2002 standard [ 4 ] due to an insufficient α-santalol content (<41%).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The oil examined in our study had an α-santalol content slightly lower than literature values of Santalum album oils ( Table 3 ) but higher than the oil obtained from Santalum spicatum . The β-santalol content approximated that determined by Kačániová et al [ 3 ], Panto et al [ 26 ] and Góra and Gibka [ 27 ]. Our results confirm that the examined oil was obtained from Santalum album ; however, it does not fulfill ISO 3518:2002 standard [ 4 ] due to an insufficient α-santalol content (<41%).…”
Section: Discussionsupporting
confidence: 74%
“…Recent years have seen a return to natural remedies, including EO, in cosmetics, personal protection products, food, aromatherapy and medicinal purposes. Research conducted in recent years has found essential oil components to have a wide range of pharmacological effects, including antimicrobial, antioxidant and relaxing properties [ 1 , 2 , 3 ]. EO’s chemical composition, and thus the pharmacological and toxicological properties, depends on the species or plant part (leaves, flowers, bark, roots, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Reduction in consumption of antimicrobials in human and veterinary medicine may minimize the problems related to the spread of antimicrobial resistance. Previous reports showed the antimicrobial activity of EOs against different microorganisms, including human and animal pathogens, from the perspective of applications in aquaculture [ 6 , 7 , 11 , 12 ]. EOs could be a promising agent in fish health, since their antimicrobial and immunomodulating properties have been described.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial effects against such different fish pathogens and contaminants as Aeromonas spp., Enterobacter spp., Pseudomonas pp., Vibrio spp., etc. have been recorded with therapeutic application of EOs as recommended previously [ 11 , 12 , 13 , 14 ]. However, the diversity of fish microbiota and chemical composition of Eos, as well as the different antimicrobial effects of the EOs tested indicates the need for further research into these antimicrobial activities.…”
Section: Introductionmentioning
confidence: 99%
“…has the ability to colonize the reproductive system and to affect its structure and functions. Kačániová et al [ 18 ] focused on the antibacterial effects of 14 selected EOs against 50 Staphylococcus spp. cultures isolated from human semen.…”
mentioning
confidence: 99%